PENGARUH LAYANAN SISTEM INFORMASI AKADEMIK (SIAKAD) TERHADAP TINGKAT KEPUASAN MAHASISWA - Muhammad Yasin; Muhammad Ilham (Al-Rabwah, 2022)
This study aims to determine how much influence the Academic Information System Service (SIAKAD) has on the level of student satisfaction of the Tarbiyah Department of STAI Sangatta East Kutai. The population in this study were all students majoring in Tarbiyah STAI Sangatta East Kutai, totaling 414 students. Researchers took random sampling so that a sample of 80 students was obtained. This study uses quantitative methods. In collecting data, a questionnaire was used to find out data about academic information system services (Siakad) and satisfaction. Furthermore, the researcher's data analysis technique used a simple Linear Regression formula. The results of the simple linear regression test in this study obtained a constant value (a) of 40,833 which contained that the consistent value of the SIAKAD service variable was 40,833, while the value of student satisfaction (b/regression coefficient) was 0.361, so the simple linear regression equation could be written Y= 40,833+ 0.361X which means that the effect of variable X on variable Y is positive. In the ANOVA table results of simple regression analysis, a significance value of 0.000 <0.05 is obtained and it is known that the count value in the coefficient table of the simple linear regression analysis test is 5.902 > the table value of 1.66, which means that the SIAKAD service variable (X) has an effect on student satisfaction variables ( Y). In the summary table of the simple linear regression analysis test model, it is obtained that a value (R) of 0.556 has a significant effect and an R Square value of 0.309 which means that this study has a positive effect of 30.9% or rounded up to 31%.